Propuesta de un modelo de diagnóstico para la determinación de la madurez digital de una empresa. - Pachacama Cajamarca, Jéssica Esthefanía (2021)
The exponential growth of technology, in addition to the crisis generated by the Covid-19 pandemic, has forced companies to adopt new digital trends in their production processes to transform their business model and survive in this environment. business level is characterized by hyper-connectivity and the search for greater customer satisfaction, the same customer who, thanks to technology, has changed his way of life, his customs and habits to fit into the digital environment. The new business models based on the digitization of their processes are constituted in search of continuous improvement, innovation, digital culture, personalization and immediacy of the product. That is why the development of a model for the diagnosis of digital maturity was proposed, to help companies start their digital transformation process, since it is currently not an option but something essential to avoid being absorbed. by competition and stay in the market. To obtain this model, the deductive method was used, which allowed a study of the existing models and analysis to establish the dimensions that can be applied for the digital evaluation of the industries of Ecuador. It was determined that the necessary criteria to evaluate digital maturity are: strategy and organization, intelligent factory, intelligent operations, intelligent solutions and customer experience; to evaluate the criteria set out above, different techniques and instruments were used such as: questionnaire in Google forms and Excel in order to better interpret the results. Once the model was designed, the validation was carried out in a flower company, which obtained the following results: strategy and organization 80%, intelligent factory 48.5%, intelligent operations 42.5%, intelligent solutions 50% and experience of the client 60%; resulting in an intermediate level of the digital maturity model established in the project.